Study on some groups of microorganism during the forest rehabilitation process in Song Ma district, Son La province - Quyen, Nguyen Thi; Sinh, Nguyen Van (Academia Journal of Biology, 2015)
The paper has made assessement on changes of some soil microorganism groups during the process of forest rehabilitation after shifting cultivation and after clear cutting in Song Ma district, Son La province. Sampling has been made in forest areas naturally regenerated for 4-6; 9-11; 14-16 and above 20 years after shifting cultivation and after clear cutting. The results have shown that the total aerobic bacteria, the total actinomycetes and the total microfungi have increased from the rehabilitation stage of 4-6 years (3.12×102; 1.23×103 and 8.05×102 CFU/g respectively in forest areas after shifting cultivation and 4.25×104; 2.32×103 and 7.32×103CFU/g respectively in forest areas after clear cutting) to the rehabilitation stage of ≥ 20 years (3.54×105; 2.23×104 and 2.51×104 CFU/g respectively in forest areas after shifting cultivation and 4.35×106; 2.72×105 and 5.46×105 CFU/g respectively in forest areas after clear cutting). The capacity in free nitrogen fixation, in cellulose decomposition, in phosphates decomposition, and in polysaccharide production of the aerobic bacteria, of actinomycetes, and of microfungi is lowest during the first forest rehabilitation stage (4-6 years), then it grows and reaches the highest value during the stage of≥20 years (5.60×103; 2.75×104; 2.10×103; 1.36×104 CFU/g respectively in forest areas after shifting cultivation and 5.24×103; 3.14×105; 4.27×104; 5.39×104 CFU/g respectively in forest areas after clear cutting).